Teboil Service Station - Architecture Beyond Philosophical Ideas - Mikko Heikkinen (Oz, 1996)
We knew that there could be trouble at the border. Ten minutes driving east from Hamina, the last town before Russia, we saw the end of the line. Simo has read from the morning papers that the Russian frontier guard has introduced a new form for trucks, messing up all traffic traveling east. Ed. note: Project by Heikkinen-Komonen Architects)